(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the ecological importance of surface and groundwater and their potential for economic use. It discusses the role of water resources in maintaining natural balance, sources of pollution, and problems arising from anthropogenic impacts. Furthermore, practical recommendations are provided for sustainable management, water quality monitoring, and efficient use of water bodies. The article serves as a supplement to research in ecology and water management fields aimed at conserving and effectively managing water resources.